OsWRKY72 enhances salt tolerance in rice via SKC1-mediated Na+ regulation - Cheng Li; Ju Guan; Wen-Hua Liang; Shu Yao; Lei He; Xiao-Dong Wei; Ling Zhao; Li-Hui Zhou; Chun-Fang Zhao; Qing-Yong Zhao; Zhen Zhu; Sheng-Dong Huang; et al. (Plant Stress, 2025)
Soil salinity threatens crop yields, but the molecular basis of crop tolerance to salt stress remain not fully understood currently. This study establish OsWRKY72 enhances salt tolerance in rice via SKC1-mediated Na+ regulation. As a group IIc WRKY transcription factor, OsWRKY72 does not possess canonical transcriptional activation domains, and demonstrates nucleus-specific localization. RT-qPCR analysis revealed that OsWRKY72 was expressed in the roots, leaves, leaf sheaths and panicles​​ of rice, and its expression was induced by salt stress in most rice varieties. Promoter analysis combined with RT–qPCR data indicates OsWRKY72 is involved in various abiotic stress response processes, including salt, ABA, and drought. The oswrky72 mutant exhibited heightened salt sensitivity, evidenced by reduced biomass, chlorophyll content, and lower K+/Na+ in shoots under salinity compared to wild-type (WT). Mechanistically, OsWRKY72 directly binds the W-box in the SKC1 promoter to regulate Na+ transport, as demonstrated by promoter binding and ion content analyses. These findings not only establish OsWRKY72 as a pivotal transcriptional regulator in rice salt tolerance but also provide a theoretical foundation for the molecular genetic breeding of salt-tolerant rice.